THE ISSUES OF TRANSLATION TEXT STRATEGIES (Conferencea, 2023)
The issue of text translation strategy revolves around the different approaches and techniques used in the process of translating text from one language to another. Translators have many difficulties in accurately and efficiently communicating the meaning, style and cultural nuances of the source text. This article explores the importance of translation text strategy and highlights the various approaches widely used by translators.